1981
DOI: 10.1161/01.res.49.3.718
|View full text |Cite
|
Sign up to set email alerts
|

Inotropic actions of isoproterenol in cat ventricular muscle. Effects of extracellular potassium.

Abstract: SUMMARY The inotropic actions of isoproterenol in cat papillary muscles or trabeculae bathed in a salt solution containing 4 mM KCl were compared to those in similar muscles bathed in a salt solution containing 22 mM KCl. Although isoproterenol evoked the same increase in force of contraction in both groups of muscles, the time course of contraction differed markedly. In muscles bathed in 4 mM KCl, isoproterenol caused a concentration-dependent decrease in time-to-pealt force, but in muscles bathed in 22 mM KC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

1985
1985
1991
1991

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 20 publications
2
6
0
Order By: Relevance
“…Since a low stimulation frequency secured the absence of a stimulation-dependent sodium load with the ensuing continuous calcium uptake through NaCa exchange, it could be assumed that the calcium stored in the release compartments of the sarcoplasmic reticulum (the junctional SR) had accumulated only from previous activity. In accordance with observations under comparable experimental conditions (16,34), it was found that increased potassium concentration blocks an early contraction component, the amplitude of which is determined by the degree to which the SR had been previously loaded with calcium (20,21). The present results show that the elevated [K+]o does not suppress the early contraction component if sufficiently high stimulation frequencies are used, as evidenced by test contractions elicited shortly after a low frequency contraction.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Since a low stimulation frequency secured the absence of a stimulation-dependent sodium load with the ensuing continuous calcium uptake through NaCa exchange, it could be assumed that the calcium stored in the release compartments of the sarcoplasmic reticulum (the junctional SR) had accumulated only from previous activity. In accordance with observations under comparable experimental conditions (16,34), it was found that increased potassium concentration blocks an early contraction component, the amplitude of which is determined by the degree to which the SR had been previously loaded with calcium (20,21). The present results show that the elevated [K+]o does not suppress the early contraction component if sufficiently high stimulation frequencies are used, as evidenced by test contractions elicited shortly after a low frequency contraction.…”
Section: Discussionsupporting
confidence: 92%
“…Only a slight increase in force remained during the first 100 ms, after which a phasic contraction developed which reached its peak at about 200 ms after the stimulus. Similar observations have been made in high KC1 solutions with guinea-pig papillary muscles in the presence of histamine (16) and with cat papillary muscles in the presence of isoprenaline (34). This indicates that at low contraction frequencies, and especially under Table 1).…”
Section: Extracellular Potassium Selectively Suppresses An Early Contsupporting
confidence: 85%
“…The contrasting inotropic actions of quinidine (and Org 6001) on contractions in normal as compared with depolarized atrial preparations raise questions regarding the possible different mechanisms of electromechanical (E-C) coupling in the two situations. Wiggins (1981) has provided strong evidence to suggest that in potassium depolarized cardiac muscle, 'slow' action potentials induced by isoprenaline allow the muscle to utilize calcium directly from extracellular sources for contraction. In contrast, in nondepolarized muscle, with functional fast Na' channels, intracellular calcium stores are ofprimary importance.…”
Section: Discussionmentioning
confidence: 99%
“…Wiggins (1981) has provided strong evidence to suggest that in potassium depolarized cardiac muscle, 'slow' action potentials induced by isoprenaline allow the muscle to utilize calcium directly from extracellular sources for contraction. In contrast, in nondepolarized muscle, with functional fast Na' channels, intracellular calcium stores are ofprimary importance.…”
Section: Electrophysiological Effects In Depolarized Atriamentioning
confidence: 99%
“…Gulch et al [12] showed the effect of urapidil on action potentials in normal Tyrode solution only at concentrations higher than 10 .3 M. They speculated that it had an effect on the slow inward Ca 2+ current because of its suppression of contactile force. Since contractile force of muscle can be influenced not only by the Ca 2+ current, but also by some other mechanisms that affect the stored Ca 2÷ [16], such as the Na ÷ current inhibition through Na÷-Ca 2÷ exchange, and Na÷-K ÷ ATPase inhibition [17][18][19], the information on muscle contraction seems to provide insufficient evidence for suppression of the Ca 2+ current.…”
Section: Discussionmentioning
confidence: 99%